Comparative IR spectral characteristics of humic acids from peats of different origin in the Tomsk area; Pharmaceutical Chemistry Journal; Vol. 43, iss. 7 - Gostishcheva M. V.; Belousov M. V. Mikhail Valerievich; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Ismatova R. R.; Dmitruk S. E. (2009, 2009)
Title screen